Glossary of Calculus Facts

Start Studying! Add Cards ↓

f(x)= cx
f'(x)= c
f(x)= g(x)+- h(x)
f'(x)= g'(x) +- h'(x)
f(x)= gh
f'(x)= f'(x)*g(x)+g'(x)*f(x)
f(x)= f/g
f'(x)= [f'(x)*g(x)- g'(x)*f(x)] /g^2(x)
f(x)= c
f'(x)= 0
f(x)= x^n
f'(x)= nx^(n-1)
f(x)= x
f'(x)= 1
f(x)= |x|
f'(x)= x/|x| *x'
f(x)= lnx
f'(x)= (1/x)*x'
f(x)= e^x
f'(x)= (e^x)x'
f(x)= logaX
f'(x)= (1/lnA*x)x'
f(x)= a^x
f'(x)= (lnA * a^x)x'
f(x)= sinx
f'(x)= (cosx)x'
f(x)= cosx
f'(x)= (-sinx)x'
f(x)= tanx
f'(x)= (sec^2X)x'
f(x)= CotX
f'(x)= -Csc^2X * x'
f(x)= SecX
f'(x)= SecX * TanX * x'
f(x)= CscX
f'(x)= -CscX * CotX * x'
f(x)= arcsinX
f'(x)=(1/sqrt 1-x^2 ) * x'
f(x)= arccosX
f'(x)= (-1/sqrt 1-x^2 ) * x'
f(x)= arctanX
f'(x)= (1/ 1+x^2) * x'
f(x)= arccotX
f'(x)= ( -1/ 1+x^2) * x'
f(x)= arcsecX
f'(x)=(1/ x * sqrt x^2 - 1) * x'
f(x)= arccscX
f'(x)=(-1/x * sqrt x^2 - 1) * x'

Add Cards

You must Login or Register to add cards